Model Komunikasi dalam Sejarah Teologi Misi - Jun Lempoy; Chilthy Sondakh (Program Studi Misiologi dan Komunikasi Kristen, 2023)
This study aims to analyze communication models in the history of mission theology as material for reflection on the existence of Christianity. In order to achieve this goal, the development of mission theology in its history must be re-examined to find ways of doing mission theology in every era or age of Christianity. Then the science of communication will also analyze the model and even the appropriate means or media of communication to convey information about the gospel message. This research uses a descriptive qualitative approach because the methods used have the aim of exploring and understanding the meaning of social problems. Library research is deliberately chosen to achieve goals by utilizing printed and electronic books, journals, and websites that can be accounted for by including the sources. The results of the study describe that there are two communication models that are generally applied in the history of mission theology, namely the Aristotle model of communication which involves three elements in the communication process, namely the speaker, the message and the listener. Then Harold Lasswell's communication model involves five elements in the form of question words, namely who, says what, with what media, to whom and with what impact. Christians as messengers can reflect the gospel message to those who are lost, neglected and separated so that the impact is real through ministry, healing and reconciliation.